A spectatorial dramaturgy, or the spectator enters the (ethical) frame. (1st March 2010) - Keefe, John
This essay attempts to raise certain issues considered as an ethos of spectatorship seeking to place the knowing experience of the spectator in relation to the stage. Six sections characterizing an ethics of recognition, looking, materiality, complicity and empathy, participation and imagination, and attending show how these work together to construct a spectatorial dramaturgy. It is argued that such a dramaturgy is empirical, is an ethical economy of regard rooted in the material and social body in mutual and reciprocal concert; that it rests on the complicit, knowing empathetic imagination located and manifested in the engaged but distanced spect-actor as agent who witnesses the work of the actor in the arena we call theatre. Therefore, this relationship between a presented mise-en-scne and the always-present spectator makes the spectator always active in some way or other. An ethical spectatorial dramaturgy is the work of the actions of spectator(s) within the weave of the theatre event.